Back Cover: Quantitative Determination and Comparison of the Surface Binding of Phosphonic Acid, Carboxylic Acid, and Catechol Ligands on TiO2 Nanoparticles (Chem. Eur. J. 38/2016). Issue 38 (21st July 2016) - Zeininger, Lukas; Portilla, Luis; Halik, Marcus; Hirsch, Andreas
Abstract : A systematic investigation of wet‐chemical adsorption, desorption, co‐adsorption, and exchange behavior of phosphonic acid, carboxylic acid and catechol monolayers on the surface of titanium oxide nanoparticles is presented. The reported procedure provides a toolbox to identify optimal monolayer–surface combinations and to evaluate critical parameters, such as monolayer robustness, ligand exchange rates, or targeted mixed assembly of functionalities, and should be applicable to many other colloidal metal oxide materials. More information can be found in the Full Paper by A. Hirsch et al. onpage 13506 ff.